ANALISIS DAYA DUKUNG EKOLOGI UNTUK PENGEMBANGAN BUDIDAYA RUMPUT LAUT DI BAGIAN UTARA TELUK BONE - Taslim Arifin; Waluyo Waluyo (Diponegoro University, 2018)
Abstract : Waters carrying capacity in seaweed (Eucheuma cottonii) cultures should be a concern for optimum seaweed culture. Carrying capacity can determine by ecological footprint (EF) analysis, which in this research use production footprint. This research on Mei 2015 (1sttransitionalseason) and September 2015 (2ndtransitionalseason) in Luwu and Palopo, South Sulawesi. Map and land use analyzed with GIS (Geographic Information Systems).The results showed that theecological footprint production (EFP)in Luwu waters is 67.88 ton/capita/year, or equivalent to 235,823.93 tons/year.Based on the analysis of the availability of water for seaweed is 59,781.79 hectares, it can produce seaweed (biocapacity) for 1,437,779.60 tons/year and the number of farmers that allows for use the waters is 21,432 capita. The ecological footprint production (EFp) in Palopo waters is 3.08 ton/capita/year, or equivalent to 4,589.99 tons/year. Water availability analysis is 1,771.41 hectares are able to produce seaweed (biocapacity) for 18,287.46 ton/year and the number of farmers that allows for use the waters is 635 farmers capita. The results comparison between biocapacity and ecological footprint, ecological status for Luwu and Palopo waters are still in sustainable use.